‘But I have a cat, I have to talk to her now’: a qualitative study on reasons for not participating in guideline-based aphasia therapy from the perspective of patients in German-speaking countries - Susann May; Felix Mühlensiepen; Laura Plotho; Robert Darkow (BMJ Open)
Objectives Clinical guidelines recommend high-frequency speech therapy for people with aphasia. Little is known about the experiences of people with aphasia with high-frequency speech therapy, why they do not receive it, what they expect from it and their general wishes and requirements for therapy. The aim of this qualitative study was to investigate the reasons for refusing high-frequency speech therapy and therapy preferences of patients with aphasia.Design An interview study with people with aphasia.Setting Interviewees were recruited via snowball sampling in different settings of healthcare system (eg, speech and language practices, self-help groups, clinics of neurorehabilitation).Participants Twenty-one people with aphasia and one relative participated in semi-structured interviews.Results We identified five categories of not using high-frequency speech therapy: patient-related factors, health system-related factors, disease-related factors, social-economic factors and organisational factors. Most reasons for non-utilisation are within the domain of the healthcare system and are partly attributable to personnel shortages in care provision and knowledge deficits among healthcare practitioners. Patient therapy preferences notably pertain to the enhancement of speech therapy services, encompassing sessions both inclusive and exclusive of family members as well as the facilitation of information dissemination.Conclusions As expected, there were indications of a lack of staff, poor care in rural areas and the influence of being affected by aphasia for a longer period on utilisation behaviour. These factors in the healthcare system and organisational factors are not unknown to those with practical experience, and some of them must and could be changed quickly. This would require a change from the established face-to-face setting in presence to sufficient digital therapy adjuvants. The results of patient-related factors could be a further reason to reflect on speech therapy and its settings and to view and treat people with aphasia in a more holistic, less language-focused way.